Influence of different agroecological systems on the chemical indicators of a cultivated soil of beans (Phaseolus vulgaris L.) - Rivero-Herrada, Marisol; Gutiérrez-Rivero, Eduardo; Granados-Rivas, Yanila Esther; Cesar Cristóbal (REVISTA TERRA LATINOAMERICANA, 2020)
The agroecological system has an important impact on the nutritional status of the soil, which depends on its preparation and the plants that are grown. The aim of this work was to evaluate the influence of different agroecological systems on the chemical indicators of a soil cultivated with beans (Phaseolus vulgaris L.). An experimental design of randomized blocks, eight treatments and four replicates, was used. The treatments were cover plants: jack bean (Canavalia ensiformis, Adans.), velvet bean (Mucuna pruriens), pigeon pea (Cajanus cajan (L.) Mill sp.), and crotalaria (Crotalaria sp. L.) planted in two cultivation systems: monoculture and associated with millet (Pennisetum glaucum L.), and two systems of soil preparation: conventional and direct seeding. The chemical indicators evaluated were: pH, organic matter, macro and micro nutrients (P, K, Ca, Mg, Fe, Mn, and Zn) and the yield in the bean crop. The direct sowing system had influence on the chemical indicators of the soil, decreased pH (5.26), high contents of Ca and K, with values of 1.64 and 73.21 mg kg-1 respectively, with regard to the conventional system. Micronutrients Cu and Zn had signif icant values of 0.97 and 1.38 mg kg-1 respectively, with regard to the conventional system. Mg and K contents reached values very close to those of natural soil. In bean crop yield, the jack bean crop was highlighted with the highest number of pods per plant (14.25), grains per pods (5.93), grains per plant (84) and a yield of 4.4 Mg ha-1.